THE RELATIONSHIP BETWEEN FAMILY COMMUNICATION PATTERNS AND THE INCIDENCE OF DEPRESSION IN ADOLESCENTS - Giawa, Desyanifransisca; Niken Yuniar Sari; Nurul Huda (Jurnal Pinang Masak, 2023)
Mental health problems are very likely to occur in people who are adolescents. Poor communication between parents and adolescents can cause mental health problems, namely depression in adolescents. This study aims to determine the relationship between family communication patterns and depression of adolescents. This study used a quantitative research method with a cross sectional approach. The research sample was adolescents at SMA 8 Pekanbaru, as many as 308 people who were recruited using a stratified random sampling technique. The measurement tools used were Revised Family Communication Pattern (RFCP) and Children Depression Inventory (CDI). The statistical analysis used the chi square test. The results showed the most of respondents were female (56.8%), the most of respondents were 16 years old (40.9%), the most of respondents' family communication pattern were consensual (61.0%) and the most of respondents had depressive symptoms (50.6%). Based on the chi square test, it was concluded that p value = 0.003 (<0.05) means that there is a relationship between family communication patterns and depression of adolescents. Based on the results of the study, it is hoped that the school can actively facilitate ways to solve mental health problems, prevention strategies and appropriate treatment to overcome depression in adolescents and to the community can know the well family communication patterns so as to prevent mental health problems, especially depression in adolescents.